(untitled) (International Journal of Food and Nutritional Sciences, 2023)
ABSTRACT: The author of this paper offers a fresh perspective on African women fighting with men in this struggle. The researcher aims to demonstrate that Ogola departs from the traditional path of women being subdued, inferior, and abused in The River and the source by showing them as bold, intelligent, self-assertive, and cooperative while demonstrating a great deal of love, respect, and understanding with men. The study will also follow the struggles of women throughout a number of generations against all the hardships they face inside Kenyan society. Here, the womanist aspect of the female characters personalities will be highlighted by analyzing how they interact with their male counterparts in their stories. The stereotypical image of African women is challenged by the womanist approach. By closely examining the text, the study also explores the author’s different perspectives of integration, solidarity, and complementarities between the two genders. She uses a range of literary techniques, such as characterization, symbols, and foreshadowing, to further support her vision of a new integrated society and to convey the novel’s theme.